Simple Microdilution Test for Detection of Metallo-β-Lactamase Production in Pseudomonas aeruginosa - Migliavacca, Roberta (American Society for Microbiology, 2002)
A microdilution test measuring imipenem MICs in the presence or absence of a mixture of EDTA plus 1,10-phenanthroline was developed and tested on 190 Pseudomonas aeruginosa isolates, including 18 VIM- and 4 IMP-type metallo-β-lactamase (MBL) producers. The chelator mixture reduced by fourfold or more the imipenem MICs for MBL producers, while a lower effect or no effect was usually observed with MBL nonproducers.